Pengaruh Perbandingan Ekstrak Okra Hijau (Abelmoschus esculentus L.) dan Karagenan Terhadap Karakteristik Permen Jeli - Tania Janice, Faustine; Kartika Pratiwi, I Desak Putu; Sri Wiadnyani, Anak Agung Istri (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2022)
This study aims to determine the effect of comparison between green okra extract and carrageenan on the characteristics of jelly candy and to get the right ratio to produce jelly candy with the best characteristics. The design used in this study was a completely randomized design with treatment consisting of 5 levels of green okra extract and carrageenan, namely : (42%: 8%), (43%: 7%), (44%: 6%), (45%: 5%), and (46%: 4%). Each was repeated 3 times to obtain 15 experimental units. The data were analyzed by analysis of variance and if there was a significant effect, the Duncan Multiple Range Test were perfomed. The results showed that ratio of green okra and carrageenan had a significant effect on texture, moisture content, crude fiber content, antioxidant capacity, texture sensory, taste, and overall acceptance. The ratio of green okra extract 44%and carrageenan 6% produced the best characteristics, texture 17.9 N, moisture content 10.52%, crude fiber content 1.15%, antioxidant capacity 279.76 mg GAEAC/100g, color liked, aroma neither like nor dislike, taste liked, texture liked and very chewy, and overall acceptance liked.